2021
DOI: 10.1186/s43162-021-00044-1
|View full text |Cite
|
Sign up to set email alerts
|

Neglected reactive arthritis complicated by bilateral hip and temporomandibular joints ankylosis after a suspected tetanus infection: a case report

Abstract: Background Reactive arthritis had been reported to occur after various vaccinations, including the tetanus toxoid vaccine; here, we report a case of ankylosing arthropathy suggested to be a complication of missed neglected reactive arthritis after tetanus infection. Case presentation A healthy 20-year-old woman presented with subtrochanteric right femoral fracture; imaging studies showed bilateral ankylosed hip, kyphoscoliosis, bilateral fused temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[54] Mahran et al showed the significant impacts of methanolic leaf powder extracts of M. koenigii and walnut against alloxan induced diabetes in murine models. [55]…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…[54] Mahran et al showed the significant impacts of methanolic leaf powder extracts of M. koenigii and walnut against alloxan induced diabetes in murine models. [55]…”
Section: Antidiabetic Activitymentioning
confidence: 99%